2015
DOI: 10.5688/ajpe79344
|View full text |Cite
|
Sign up to set email alerts
|

Developing Pharmacy Student Communication Skills through Role-Playing and Active Learning

Abstract: Objective. To evaluate the impact on pharmacy students of a communication course, which used roleplaying to develop active-learning skills. Design. Students role-playing pharmacists in patient care scenarios were critiqued by students and pharmacist faculty members. Grading was performed using the rubric inspired by Bruce Berger's Communication Skills for Pharmacists. Written skills were evaluated using student written critique questionnaires. Students completed precourse and postcourse self-assessment surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Continuous feedback from peers gave the students an opportunity to sharpen their communication skills in a safe and supportive classroom environment. 12,13 It is evident from our study findings that students in both groups showed significant improvement in post-test scores for almost all the parameters. This was a welcome finding which re-iterated our belief that it is vital to instil in our students, all important skills needed by a medical graduate in today's world especially in context to pharmacology.…”
Section: Discussionmentioning
confidence: 52%
“…Continuous feedback from peers gave the students an opportunity to sharpen their communication skills in a safe and supportive classroom environment. 12,13 It is evident from our study findings that students in both groups showed significant improvement in post-test scores for almost all the parameters. This was a welcome finding which re-iterated our belief that it is vital to instil in our students, all important skills needed by a medical graduate in today's world especially in context to pharmacology.…”
Section: Discussionmentioning
confidence: 52%
“…Presenting their findings to their peers provided students with the opportunity to practise their public-speaking skills in a safe and supportive setting. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Developing an instrument representing different characteristics of teacher learning in ELT context for the current pharmacy education is important. There is a need to provide better language development opportunities for pharmacy graduates to enable them to perform as quality medical professionals (Kimberlin, 2006;Luiz Adrian, Zeszotarski, & Ma, 2015). Many studies have reported the application of different languagerelated scales to measure the students' performance level in pharmacy (Bradshaw, Tomany-Korman, & Flores, 2007;Dilworth, Mott, & Young, 2009;Schwappach, Massetti, & Gehring, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These measures do not effectively cover the issues of language teaching, and learning in the field of pharmacy education rather covered alternative instructional delivery. Even the alternative did not include pharmacy concepts in the relation of language learning and teaching (Adrian et al, 2015;Dang, Truong, & Wade, 2019;Syakur, Junining, & Mubarok, 2020). This study specifically contributes to this gap by validating the ELTLS instrument for assessing the English language teaching and learning outcomes of students and also the factors influencing language teaching and learning implementation in the field of pharmacy education from developing country perspective.…”
Section: Introductionmentioning
confidence: 99%